A Game Theoretic Analysis of the Conditions of Knowledge Transfer by New Employees in Companies - Sidonia von Ledebur (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2006)
The availability of knowledge is an essential factor for an economy in global competition. Companies realise innovations by creating and implementing new knowledge. Sources of innovative ideas are partners in the production network but also new employees coming from another company or academia. Based on a model by HECKATHORN (1996) the conditions of efficient knowledge transfer in a team are analysed. Offering knowledge to a colleague can not be controlled directly by the company due to information asymmetries. Thus the management has to provide incentives which motivate the employees to act in favour of the company by providing their knowledge to the rest of the team and likewise to learn from colleagues. The game theoretic analysis aims at investigating how to arrange these incentives efficiently. Several factors are relevant, especially the individual costs of participating in the transfer. These consist mainly of the existing absorptive capacity and the working atmosphere. The model is a 2x2 game but is at least partly generalised on more players. The relevance of the adequate team size is shown: more developers may increase the total profit of an innovation (before paying the involved people) but when additional wages are paid to each person a greater team decreases the remaining company profit. A further result is that depending on the cost structure perfect knowledge transfer is not always best for the profit of the company. These formal results are consistent with empirical studies to the absorptive capacity and the working atmosphere. – – Die Verfügbarkeit von Wissen und die Fähigkeit zur schnellen Anwendung von wissenschaftlichen Neuerungen stellen heute einen zentralen Erfolgsfaktor von Volkswirtschaften dar. Unternehmen machen mit Wissensgenerierung und -umsetzung Innovationen. Anregungen dazu kommen von Partnern im Produktionsnetzwerk, aber auch von neuen Mitarbeitern, die aus der Wissenschaft oder einem anderen Unternehmen in das Unternehmen kommen. Auf einem Modell von HECKATHORN (1996) basierend werden die Bedingungen effizienten Wissenstransfers in einem Team untersucht. Da Wissensweitergabe aufgrung von Informationsasymmetrien nicht kontrolliert werden kann, muß das Unternehmen entsprechende Anreize setzen. Diese lassen sich spieltheoretisch ermitteln. Mehrere Faktoren spielen eine Rolle, besonders wichtig sind die Kosten des einzelnen, die ihm bei der Teilnahme am Wissenstransfer entstehen. Das Absorptionsvermögen und die Arbeitsatmosphäre bestimmen die Kosten in erster Linie. Das Modell ist ein 2x2-Spiel, das anschließend teilweise auf mehrere Spieler verallgemeinert wird. Die Relevanz der Teamgröße wird gezeigt und das vollständiger Wissenstransfer bei hohen individuellen Kosten nicht unbedingt gewinnmaximierend für das Unternehmen ist. Diese formalen Ergebnisse unterstützen vorhandene empirische zu Absortionsvermögen und Arbeitsatmosphäre.
urn:nbn:de:gbv:3:2-1603
Keywords: C72; D83; O31; 330; Wissenstransfer; Innovation; Spieltheorie; Absorptionsvermögen; Knowledge Transfer; Innovation; Game Theory; Absorptive Capacity